2018
DOI: 10.1021/acsami.8b13634
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Gas Permeation and Diffusion in Triptycene-Based Ultrapermeable Polymers of Intrinsic Microporosity

Abstract: A detailed analysis of the basic transport parameters of two triptycene-based polymers of intrinsic microporosity (PIMs), the ultrapermeable PIM-TMN-Trip and the more selective PIM-BTrip, as a function of temperature from 25°C to 55°C, is reported. For both PIMs, high permeability is based on very high diffusion and solubility coefficients. The contribution of these two factors on the overall permeability is affected by the temperature and depends on the penetrant dimensions. Energetic parameters of permeabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 27 publications
5
47
0
1
Order By: Relevance
“…The remarkable positions of the data for the benzotriptycene-PIMs on the H 2 /N 2 , and O 2 /N 2 Robeson plots are due to very high diffusivity selectivity originating from the size-sieving behaviour of the polymers, which differentiates between gas molecules of differing effective diameters (d x ). 40 This is best illustrated by the correlation between d x 2 and the diffusivity coefficient (D x ), 55 which is steepest for PIM-BTrip and less steep for benzotriptycene PIMs that possess a substituent, although the absolute value of the diffusion coefficient is larger (Fig. 3).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The remarkable positions of the data for the benzotriptycene-PIMs on the H 2 /N 2 , and O 2 /N 2 Robeson plots are due to very high diffusivity selectivity originating from the size-sieving behaviour of the polymers, which differentiates between gas molecules of differing effective diameters (d x ). 40 This is best illustrated by the correlation between d x 2 and the diffusivity coefficient (D x ), 55 which is steepest for PIM-BTrip and less steep for benzotriptycene PIMs that possess a substituent, although the absolute value of the diffusion coefficient is larger (Fig. 3).…”
Section: Resultsmentioning
confidence: 96%
“…Furthermore, it was found that the unsubstituted benzotriptycene-based PIM (PIM-BTrip) demonstrates even greater selectivity placing its data above the proposed 2015 O 2 /N 2 , H 2 /N 2 and H 2 /CH 4 upper bounds and even above Robeson's 2008 upperbounds for CO 2 /N 2 and CO 2 / CH 4 . 40,41 Here we report on the synthesis and properties of some new members of the benzotriptycene-based PIM series ( Fig. 1), all of which demonstrate high permeability and selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…With exception of CO 2 and N 2 , which are inverted in all fresh samples but PIM-EA(H 2 )-TB, the diffusion coefficient decreases with increasing effective molecular diameter as defined by Teplyakov and Meares [46]. After ageing, the diffusion coefficient decreases with the gas diameter more markedly (Figure 5b), evidencing a stronger size selectivity of the polymers [30]. Interestingly, PIM-Trip(H 2 )-TB maintains a relatively high diffusion coefficient for smaller gas molecules upon ageing, but it becomes the most size selective, whereas PIM-Trip(Me 2 )-TB shows exactly the opposite trend, with the lowest diffusion coefficient and the lowest size selectivity.…”
Section: Membrane Preparation and Gas Permeability Measurementsmentioning
confidence: 74%
“…The large fractional free-volume formed between polymer chains allows access to penetrant gases and high solubility for condensable gases such as CO 2 . At the same time, the rigid structure with impeded chain mobility enhances the energetic selectivity, resulting in a strong size-sieving character of these polymers [30]. When solvent-cast into films for gas permeability experiments, PIMs were found to combine both high selectivity with high permeabilities providing data that was used to define Robeson's 2008 upper bounds and those proposed in 2015 and 2019.…”
Section: Introductionmentioning
confidence: 98%
“…11 Based on our previous work, there is still some focus worth further study, such as temperature, which is an important factor that affects the microstructures and macroscopic properties, especially for some high-polarity materials. 14,15 Many studies have indicated that the effect of temperature on cavity size, 16 hysteresis, 17 conductivity, 18,19 dielectric properties, 20 straininduced crystallization 21,22 and mechanical properties 23,24 of rubbers and their composites is nonnegligible. Many properties of materials containing a large number of hydrogen bonds show more obvious temperature dependence, which results from the high temperature sensitivity of hydrogen bonds.…”
Section: Introductionmentioning
confidence: 99%